Working day and night: plastid casein kinase 2 catalyses phosphorylation of proteins with diverse functions in light‐ and dark‐adapted plastids. (20th August 2020) - Rödiger, Anja; Galonska, Johann; Bergner, Elena; Agne, Birgit; Helm, Stefan; Alseekh, Saleh; Fernie, Alisdair R.; Thieme, Domenika; Hoehenwarter, Wolfgang; Hause, Gerd; Pfannschmidt, Thomas; Baginsky, Sacha
Summary: Casein kinase 2 is a ubiquitous protein kinase that has puzzled researchers for several decades because of its pleiotropic activity. Here, we set out to identify the in vivo targets of plastid casein kinase 2 (pCK2) in Arabidopsis thaliana . Survey phosphoproteome analyses were combined with targeted analyses with wild‐type and pck2 knockdown mutants to identify potential pCK2 targets by their decreased phosphorylation state in the mutant. To validate potential substrates, we complemented the pck2 knockdown line with tandem affinity tag (TAP)‐tagged pCK2 and found it to restore growth parameters, as well as many, but not all, putative pCK2‐dependent phosphorylation events. We further performed a targeted analysis at the end‐of‐night to increase the specificity of target protein identification. This analysis confirmed light‐independent phosphorylation of several pCK2 target proteins. Based on the aforementioned data, we define a set of in vivo pCK2‐targets that span different chloroplast functions, such as metabolism, transcription, translation and photosynthesis. The pleiotropy of pCK2 functions is also manifested by altered state transition kinetics during short‐term acclimation and significant alterations in the mutant metabolism, supporting its function in photosynthetic regulation. Thus, our data expand our understanding on chloroplast phosphorylation networks and provide insights into kinase networks in the regulation of chloroplast functions. Significance Statement: We report a set of previously unknown substrates for plastid casein kinase 2 signifying a function of this kinase in the cross‐talk between photosynthetic acclimation and other chloroplast functions, such as gene expression and metabolism. Our data provide information required to understand the network underlying regulatory phosphorylations in chloroplasts.